First report of Lymnaea cousini Jousseaume, 1887 naturally infected with Fasciola hepatica (Linnaeus, 1758) (Trematoda: Digenea) in Machachi, Ecuador - Villavicencio A., Angel (2005)
Russian People’s Friendship University. Agrary Faculty. Department of Veterinary Pathology. Moscow, Russia.